2015
DOI: 10.1371/journal.pone.0133202
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Benefits of Molecular Testing for Gonorrhoea Antibiotic Resistance Surveillance in Remote Settings

Abstract: BackgroundSurveillance for gonorrhoea antimicrobial resistance (AMR) is compromised by a move away from culture-based testing in favour of more convenient nucleic acid amplification test (NAAT) tests. We assessed the potential benefit of a molecular resistance test in terms of the timeliness of detection of gonorrhoea AMR.Methods and FindingsAn individual-based mathematical model was developed to describe the transmission of gonorrhoea in a remote Indigenous population in Australia. We estimated the impact of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…decision support. Only seven articles in this series develop individual-based representations of the system of interest [47,55,56,69,72,87,96], suggesting that ABMs have been infrequently used to examine the AMU/AMR relationship at the population level. While experts decidedly agree that AMR is a 'One Health' problem requiring multi-sectoral action [7], there are few examples of inter-host models outside of strictly human contexts.…”
Section: Model Type and Contextmentioning
confidence: 99%
“…decision support. Only seven articles in this series develop individual-based representations of the system of interest [47,55,56,69,72,87,96], suggesting that ABMs have been infrequently used to examine the AMU/AMR relationship at the population level. While experts decidedly agree that AMR is a 'One Health' problem requiring multi-sectoral action [7], there are few examples of inter-host models outside of strictly human contexts.…”
Section: Model Type and Contextmentioning
confidence: 99%
“…They found that increased treatment rates could increase the spread of resistance, whereas re-treatment could slow it down. Hui et al [ 14 ] used an individual-based N. gonorrhoeae transmission model in a heterosexual host population to investigate the effect of a molecular resistance test on the time until 5% resistance are reported. None of these studies has investigated or explained the differences in the spread of antibiotic-resistant N. gonorrhoeae in MSM and heterosexual host populations.…”
Section: Introductionmentioning
confidence: 99%
“…Using an individual-based dynamic transmission model that incorporated partner treatment and which was applied to a London MSM population, Zienkiewicz et al [ 38 ] also demonstrated that AMR POCTs for NG ciprofloxacin sensitivity reduced ceftriaxone use, by 70% compared with the reference scenario. An individual-based model of molecular NG AMR test use compared with culture within an NG surveillance system in remote settings found that they substantially improved the timeliness of NG AMR detection, facilitating a faster change in recommended treatment, with potential for decreasing NG AMR impact on the wider population [ 39 ]. Fingerhuth et al [ 36 ] developed a compartmental transmission model of antibiotic-sensitive and antibiotic-resistant NG to look at proportion of resistant infections and cases averted.…”
Section: Discussionmentioning
confidence: 99%